Flourish of Proton and Carbon Ion Radiotherapy in China - Li, Yue; Li, Xiaoman; Yang, Jiancheng; Wang, Sicheng; Tang, Meitang; Xia, Jiawen; Gao, Yunzhe (Frontiers in Oncology, 2022)
Proton and heavy ion therapy offer superior relative biological effectiveness (RBE) in the treatment of deep-seated tumors compared with conventional photon radiotherapy due to its Bragg-peak feature of energy deposition in organs. Many proton and carbon ion therapy centers are active all over the world. At present, five particle radiotherapy institutes have been built and are receiving patient in China, mainly including Wanjie Proton Therapy Center (WPTC), Shanghai Proton Heavy Ion Center (SPHIC), Heavy Ion Cancer Treatment Center (HIMM), Chang Gung Memorial Hospital (CGMH), and Ruijin Hospital affiliated with Jiao Tong University. Many cancer patients have benefited from ion therapy, showing unique advantages over surgery and chemotherapy. By the end of 2020, nearly 8,000 patients had been treated with proton, carbon ion or carbon ion combined with proton therapy. So far, there is no systemic review for proton and carbon ion therapy facility and clinical outcome in China. We reviewed the development of proton and heavy ion therapy, as well as providing the representative clinical data and future directions for particle therapy in China. It has important guiding significance for the design and construction of new particle therapy center and patients' choice of treatment equipment.